Respuesta :
Answer:
x=1/6 and x=-4 are the zeroes of the given equation.
Hence, at these points we will get g(x)=0
Step-by-step explanation:
We have been given the function:
[tex]g(x)=6x^2+23x-4[/tex]
When g(x)=0 we will put g(x)=0 we get:
[tex]6x^2+23x-4=0[/tex]
We will factorize the above equation:
[tex]6x^2+24x-x-4=0[/tex]
[tex]6x(x+4)-1(x+4)=0[/tex]
[tex](6x-1)(x+4)=0[/tex]
Now we will equate both the factors to zero we get:
(6x-1)=0 and (x+4)=0
x=1/6 and x=-4 are the zeroes of the given equation.
Hence, at these points we will get g(x)=0